MENINGKATKAN KEMAMPUAN MEMBACA LANCAR SISWA MELALUI MEDIA BERMAIN ADU TEBAK - Martiah Martiah (MEDIA DIDAKTIKA, 2015)
The study was aimed to describe (1) the learning plan of reading fluently with playing guess fighting media, (2) the learning process of reading fluently with playing guess fighting media, and (3) the increase of yield learning to read fluently with the media playing guessing contest. The study was conducted in the first grade students of SDN Pandanpancur III, Deket, Lamongan. The research was designed with classroom action research (PTK) was conducted in two cycles. The results showed that an average pra-action the students’ learning outcomes was 67.8. In the first cycle, the average of students’ reading ability was 68.6 and the students’ reading ability in the second cycle increased to 74. Students who pass on pra-action were ten students or 33.3%, in the first cycle increased to 15 students or 50% and the second cycle increased to 26 students or 86.7%. Thus completeness classical reaches 80% was reached. This showed that the guess fighting media can increase the first graders’ ability in reading fluently.